Comprehensive Stability Study of Vitamin D3 in Aqueous Solutions and Liquid Commercial Products - Temova Rakuša, Žane (Pharmaceutics, 2021)
Vitamin D3 has numerous beneficial effects, such as musculoskeletal, immunomodulatory, and neuroprotective. However, its instability is the main obstacle to formulating quality products. Despite increased attention and growing use, data on vitamin D3 stability is scarce because data from individual studies is inconclusive and mostly qualitative. Therefore, we have systematically investigated the influence of various factors (temperature, light, oxygen, pH, concentration, and metal ions) on its stability in aqueous media using a stability-indicating HPLC-UV method. First-order kinetics fitted its degradation under all tested conditions except light and oxygen. In both cases, the established models in chemical kinetics were inappropriate and upgraded with the Weibull model. Metal ions and acidic conditions had the main destabilizing effect on vitamin D3 in aqueous media, but these solutions were successfully stabilized after the addition of ethylenediaminetetraacetic acid (EDTA), ascorbic acid, and citric acid, individually and in combination. EDTA showed the most significant stabilizing effect. Synergism among antioxidants was not observed. Our findings on vitamin D3 instability in aqueous media also correlated with its instability in commercial products. Vitamin D3 aqueous products require proper stabilization, thereby signifying the importance and contribution of the obtained results to the formulation of stable and quality products.